NASA: The First 25 Years - Goodtimes Home Video Corp. (1987)
This is an overview of NASA's history, beginning with its founding in 1958 and leading up to its 25th anniversary in 1988. This video contains footage of many important moments in NASA's history, including the first spacewalk, the Apollo 11 moon landing, the reusable Columbia space shuttle, and Spacelab.
Keywords: United States. National Aeronautics and Space Administration; Project Mercury (U.S.); Project Gemini (U.S.); Project Apollo (U.S.); Skylab Program; Viking Mars Program (U.S.); Artificial satellites in telecommunication; Space flight; Voyager Project; Columbia (Spacecraft); Space Shuttle Program (U.S.)